MARKETING CONTENT ANALYSIS ON THE TIKTOK APPLICATION PLATFORM (CASE STUDY OF THE TIKTOK ACCOUNT @SOLOCARIFOOD) - Triana Hasty Kusuma; Mar'atus Sholikah (Sean Institute, 2023)
Analysis of marketing content on the TikTok @Solocarifood account will provide insight into the types of content that are most effective in attracting the attention of a very diverse number of TikTok users. In addition, we will analyze the account's style and approach in conveying their marketing messages, including the use of music, visual effects and interesting narratives. Qualitative research methods are used to understand the marketing content of the TikTok @SolocariFood account and its impact on users. The steps in this study include sample selection, data collection through interviews, observation, and content analysis, data analysis using a thematic or narrative approach, interpretation of results, and preparation of reports. several important discussions that provide in-depth insight into the success of their marketing strategy on the TikTok platform. First, the author's analysis shows that the content marketing account @SolocariFood has succeeded in achieving their marketing goals. In conclusion, content marketing data analysis for the @SolocariFood account on TikTok provides valuable insights for marketers in developing effective and relevant content marketing strategies. The success of content marketing can be seen from the response, interaction, user involvement, and its influence on consumer decisions.